Morphometry, land use and cover, and land structure in the Córrego do Cervo watershed, Palmeira d’Oeste - SP - Maschio, Julia de Paula; Souza, Ândria Carolina Leite de; Lima , César Gustavo da Rocha (Technical and Scientific Journal Green Cities, 2025)
For environmental planning and management of natural resources in a river basin, it is essential to identify the morphometric aspects and the evolution of land use and coverage. This study aimed to perform morphometric and land use and coverage analysis in the Córrego do Cervo microbasin, using remote sensing technical tools and Geographic Information Systems (GIS) tools. By delimiting the basin in the ArcGIS 2018 software (ESRI, 2020), the variables for calculating the morphometric parameters were obtained. For use and coverage, the MapBiomas Project – Collection 8 for the years 1900, 2000, 2010, 2020 and 2022 was used as a database. When interpreting the morphometric parameters, it is concluded that the microbasin is elongated and with low susceptibility to flooding, as corroborated by the compactness coefficient (Kc = 1.579), the circularity index (Ic = 0.395) and the shape factor (Kf = 0.229). Through the analysis of land use and occupation, it was found that the predominance of pasture and pasture and agriculture mosaic was 47.649% and 16.207%, respectively, of the total area in 2022, which is an indication of vulnerability to erosion. In the land characterization, the predominance of small properties and the dominance of pasture in relation to other uses stood out.